Prevalence and psychosocial factors associated with serious injuries among in-school adolescents in eight sub-Saharan African countries - Richard Gyan Aboagye; Dickson Okoree Mireku; John Jackson Nsiah; Bright Opoku Ahinkorah; James Boadu Frimpong; John Elvis Hagan; Eric Abodey; Abdul- Aziz Seidu (BMC, 2022)
Abstract Background Injury is one of the major causes of death and illness among children and adolescents worldwide. We sought to investigate the prevalence of serious injury and its associated factors among in-school adolescents in eight countries in sub-Saharan Africa. Methods A sample of 14,967 in-school adolescents was drawn from the Global School-based Student Health Surveys conducted from 2012 to 2017 in eight sub-Saharan African countries. Data were collected using self-administered structured questionnaires. The prevalence of serious injuries was calculated using proportions while multivariable binary logistic regression analysis was carried out to determine the factors associated with serious injuries. Results Approximately 45% of in-school adolescents had experienced serious injuries during the past 12 months to the survey in the eight sub-Saharan African countries, with variations from 32.3% in Mauritius to 68.2% in Liberia. Adolescents who experienced bullying [aOR = 2.37, CI = 2.10, 2.68], those who engaged in physical fight [aOR = 2.14, CI = [1.87, 2.44], those who experienced an attack [aOR = 1.96, CI = [1.73, 2.22], those who felt anxious [aOR = 1.47, CI = 1.22,1.77], those who attempted suicide [aOR = 1.38, CI = 1.14, 1.65], truants [aOR = 1.33, CI = [1.17,1.51], current tobacco users [aOR = 1.42, CI = [1.01, 2.01] and current marijuana users [aOR = 1.78, CI = 1.08, 2.93] had higher odds of experiencing serious injuries. However, those whose parents or guardians respected their privacy had lower odds of experiencing serious injuries [aOR =0.78, CI = [0.68, 0.88] compared to those whose parents or guardians did not respect their privacy. Conclusion A relatively high prevalence of serious injuries among in-school adolescents was identified in the eight sub-Saharan African countries studied. Programs and interventions that target the reduction of injuries in educational institutions should take a keen interest in the factors identified in this study. To deal with injury victims, first aid services should be provided in school settings.